Comparative sensitivity of DOT - enzyme linked immunosorbent assay (DOTELISA) and the polymerase chain reaction (PCR) in the detection of trypanosome infection in tsetse flies (Glossina spp.) - Ouma, J.O.; Masake, R.A.; Masiga, Daniel K.; Moloo, S.K.; Minja, S.H.; Njuguna, J.T.; Olaho-Mukani, W.; Ndung'u, J.M. (OAU/STRC, 1999)
Dot-enzyme linked immunosorbent assay (dot-ELISA), developed for the detection and identification of trypanosome species in tsetse flies, was validated in the laboratory by comparing its sensitivity to that of the polymerase chain reaction (PCR). Tsetse flies were experimentally infected with different stocks of T. brucei and T. congolense. The flies were dissected and midgut samples tested using the two techniques alongside each other. Dot-ELISA detected 98.4 percent of T. brucei and 94 percent of T. congolense infections in tsetse midguts and was shown to detect up to a minimum of 103 trypanosomes per dot. PCR detected 97.6 percent of T. brucei-infected and 96 percent of T. congolense-infected tsetse midgut samples. These results show both the dot-ELISA and PCR as sensitive, species-specific tests for revealing trypanosome infections in tsetse flies. A limitation of dot-ELISA is that it can detect a minimum of 103 parasites as compared to PCR which detects fewer numbers of trypanosomes. However, the dot-ELISA Reported in the present study utilizes material that can easily be transported to the field and can be performed without the need for electricity. It will be a useful tool in the generation of field data on the infection rates and prevalence of trypanosome infection in the tsetse population.